Pelatihan Akuntansi untuk Meningkatkan Keterampilan Akuntansi di Era Vuca pada UPPKA Layang-Layang Palembang - Rafika Sari; Tien Yusnaini; Endah Dewi Purnamasari (Jurnal Surya Masyarakat, 2023)
The goal of the dedication of the Indo Global Mandiri University lecturers is to increase accounting knowledge which is important for business actors in order to mobilize UPPKA to prepare for business challenges, the ability to build and conduct Diera vuca businesses where UPPKA itself is a group of activities for the development of a prosperous family and family resilience to fill time and utilizing the socio-economic potential of the family by empowering the family in the social and economic fields. , maintain and control business operations . Accounting knowledge and skills are important to be improved by small entrepreneurs so they want to plan and budget their business properly with the aim of maintaining and even improving their business for the better, the implementation of trials is carried out with workshops and presentations as well as training with mild cases of transactions that occur in groups Palembang Layang Kite UPPKA small business. The result is that after questioning and answering case studies, the UPPKA small business group understands small business accounting and its application in a simple way